Description of Atetylenchus metaporus sp. n. (Nematoda: Psilenchidae) from Pakistan (Journal of Nematode Morphology and Systematics, 2012)
A new species of the genus Atetylenchus is described from soil around roots of wheat plants grown in the experimental fi eld of Ternab Agricultural Research Institute, NWFP, Pakistan. Atetylenchus metaporus sp. n. is characterized by its annulated and truncated lip region, lateral fi eld with four crenate incisures, median bulb located at 44-46% of neck length, DGO distance more than stylet length from its base, ovary refl exed, spermatheca fi lled, and long fi liform tail. A key to identifi cation of Atetylenchus species is also given.